The Triumph and Tragedy of Human Capital: Foundation Resource for Building Network Knowledge Economies - Melody, William H. (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2002)
A fundamental transformation to a global information and knowledge economy is underway, driven by dramatic changes in technologies, markets and government policies - the combination of pervasive applications of information and communication technologies and services, and the world-wide movement to market liberalisation and deregulation. People are expected to be the central resource attracting investment because knowledge is essentially produced, stored and applied by humans. Although many indicators suggest the economic well-being of people today is better than at any time in human history, global – and particularly youth - unemployment continues to increase. More balanced global liberalisation policies will tighten regulation of financial markets and liberalise agriculture, textile and labour markets. For the future, increased investment in human capital, and in access to education and training institutions is essential. The next generation Internet will make possible expanded educational networks and the global sharing of university resources. New programmes must build more productive linkages between universities and other societal institutions, and broaden the disciplinary foundations of traditional programmes. The LINK Centre is now prepared to join the international network of leading ICT policy centres, and crack the training dependency syndrome in this field. Through its support for an African network of similar centres, LINK will help create the foundation for the ultimate triumph of human capital in 21st century knowledge economies.